Potensi Pendapatan Dan Sustainability Bendi Sebagai Atraksi Wisata - Christine P.E Porajow; Martinus Sony Erstiawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The need to maintain Bendi as traditional transportation amid advances in transportation technology that reaches the wider community. The purpose of the study determines the strategy from the perspective of the government and bendi community in managing the potential tourism income and sustainability. The research method uses qualitative descriptive referring to informants who are sources from the transportation office, Tomohon city tourism office and Bendi Community as well as users or tourists who use Bendi as tourist transportation. The results obtained were analyzed using the SWOT method to determine the role of the government and determine the direction of bendi policy as a potential to increase tourism income and the sustainability of traditional transportation as a tourist attraction. In addition, bendi is still the prima donna of traditional transportation, the need for vision, mission and management of bendi by the local government which becomes an annual routine activity. The potential income of bendi attractions to become cultural heritage that involves generations and as an unemployment alleviator for local communities is an opportunity to continue to be empowered. Bendi has the potential to increase tourism transportation revenue and become a product to support the progress of small and medium enterprises. Threats faced by tourist interest, modern transportation, technological innovation in the world of transportation. The conclusion is that Bendi is one of the potential transportation income for local and foreign tourists that needs to be managed by the local government based on the vision, mission and routine activities and prepared jointly with the Bendi community and related agencies.